Senderización y señalética turística de los atractivos naturales pailones y aguas termales de Muyuyacu, de la Parroquia Rural Progreso, Cantón Pasaje, Provincia de El Oro - Cuenca Herrera, Verónica Del Cisne (2016)
Tourism is an industry that is in the process of change, showing a vigorous growth and diversification, as well as a growing sophistication of demand, which demands personalized and quality experiences. Today, tourism has become one of the world's largest economic and growth sectors. Ecuador is considered one of the most biodiverse countries, as it has a vast and unequaled natural and cultural wealth, where the diversity of its four regions has given rise to hundreds of thousands of species of flora and fauna. Reason why tourism can become an engine of socio-economic progress, through the creation of jobs, enterprises, enterprises, infrastructure and export currencies, thus benefiting the economy of its people. Passage a canton with impressive potential as it hides countless natural and cultural tourist attractions, the highest part of its territory presents a variety of tropical forests with exquisite biodiversity. Attractions that have not been able to be boosted tourist as they do not have an optimal infrastructure and at the same time the limited tourist signage has slowed the development of the same. The tourist activity, has achieved a constant dynamism in the economy of the places that possess some interesting characteristic for the tourists, this demands that those zones must be traced and signaled. In this perspective it was conducted this investigation, which has the general objective to conduct a study of the "SENDERIZACIÓN AND TOURISM SIGNAGE OF NATURAL ATTRACTIONS AND WATER HOT SPRINGS PAILONES MUYUYACU" of the aforementioned parish. This work was done in order to contribute to the tourist development of the parish and in this way boost the economy of the inhabitants of the sector. For which the following methodology was applied: in the development of the First Objective; To comply with the tourist diagnosis of the current situation of the Progreso Parish, the analytical method was used, Carla Ricaurte Quijano's authoritative matrix was adapted to the reality, and the methodology was applied for inventory of tourist attractions of MINTUR, Through the technique of direct observation, finally, the interview was carried out and the analysis of the SWOT matrix was performed to reinforce the evaluation of the diagnosis. For the second objective; Develop the proposed "SENDERIZACIÓN AND TOURIST ATTRACTIONS NATURAL SIGNAGE, PAILONES MUYUYACU WATERS AND THERMAL" deductive and inductive method was used; With the methodology of authorship of Miguel Cifuentes, was carried out the analysis of the Capacity of tourist load of the trails one and two, with the GPS was obtained the coordinates for the tracing of the trails withwhich the Base Map was elaborated, of Senderización And signage. Considering as a bibliographical source the MINTUR Corporate Signage Tourist Guide, which standardized the signage in Ecuador. Finally, in order to comply with the Third Objective, the qualitative matrix of cause-effect interaction and Leopold's environmental impact assessment matrix was applied to identify the possible significant environmental impacts that may occur in all phases of the project. In the results of the present investigation the current diagnosis of the Progreso parish was obtained, in which general data, location, political and administrative division, population, service provision, basic services infrastructure, governance, main economic activities, problems Social and tourism potential that it possesses; Likewise, georeferenced maps of the Senderización and Señalética of trail one were designed; Which according to calculations of the Load Capacity can receive 118 people approximately per day, and georeferenced maps of the Senderización and Señalética of the path two; Which according to calculations of the Load Capacity can receive approximately 42 people per day. The respective tourist activity pictograms, approach signs and destination information billboards were designed for trails one and two, which together total a total of 13 signs and, finally, the application of the project will undoubtedly generate a negative environmental impact Of low range to the factors soil and landscape in relation to the other factors. Likewise, a positive impact will be generated, as workplaces will be implemented and the quality of life of the Community will be improved. With this information it is established that the Parroquia Rural Progreso, site Muyuyacu has a great tourist potential, which has the most natural attractions of the parish, which are not used by tourists; so it is concluded that the study of "SENDERIZACIÓN AND TOURISM SIGNAGE OF NATURAL ATTRACTIONS AND WATER HOT SPRINGS PAILONES MUYUYACU" is an alternative to promote the development of tourism and improve the quality of life of the population. Following the respective recommendations, it was suggested to the Progreso Parish GAD, to implement the project of senderización and tourist signage for the natural attractions Pailones and Aguas Termales de Muyuyacu, in order to generate benefits for the community and contribute to the conservation and protection of the attractions.